The Influence of MSMEs on Economic Growth in Jayapura City - Rante, Yohanis (East Asian Journal of Multidisciplinary Research, 2024)
The research was conducted in Jayapura City by utilizing quantitative methods. In this study using time series data. Time series data is data that is organized based on the time sequence of events. The time series data includes all MSMEs in 21 sub-districts registered at the Jayapura City Office of Cooperative Trade and Micro Business during 2015-2022. The results showed that the growth of MSMEs in Jayapura City played an important role in the economic growth of Jayapura district / city by increasing the Gross Regional Domestic Product (GRDP). The effect of MSMEs on economic growth, showing the results of the tcount value of the variable number of MSMEs on GRDP of -8.9259 with a probability value of 0.000. Because the probability value is smaller than 0.05, it can be concluded that the growth in the number of MSMEs is significant in influencing the growth of GRDP in Jayapura city. The negative regression coefficient shows that the growth in the number of MSMEs is inversely proportional to the growth of GRDP in Jayapura city. When the number of MSMEs has decreased since 2021, the GRDP of Jayapura city has actually continued to increase.